2016
DOI: 10.1097/fbp.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

A role for sigma receptors in stimulant self-administration and addiction

Abstract: Sigma-1 receptors (σ1Rs) are structurally unique intracellular proteins that function as chaperones. σ1Rs translocate from the mitochondria-associated membrane to other sub-cellular compartments, and can influence a host of targets, including ion channels, G-protein-coupled receptors, lipids, and other signaling proteins. Drugs binding to σRs can induce or block the actions of σRs. Studies indicate that stimulant self-administration induces reinforcing effects of σR agonists, due to dopamine transporter action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 88 publications
1
61
0
Order By: Relevance
“…Therefore, cocaine and other stimulants may engage additional mechanisms that would participate in specific addictionrelated phenotypes. In that regard, a stream of studies demonstrates that cocaine also engages mechanisms that are dependent on σ1, but independent of DA signaling, and which contribute to cocaine addiction [10]. For example, animals with cocaine experience, but not after experience with food reinforcement, self-administer σ1 agonists (e.g., PRE-084 and (+)-Pentazocine) [76] at doses that do not induce DA release in the NAcSh [77] (reviewed in [10]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, cocaine and other stimulants may engage additional mechanisms that would participate in specific addictionrelated phenotypes. In that regard, a stream of studies demonstrates that cocaine also engages mechanisms that are dependent on σ1, but independent of DA signaling, and which contribute to cocaine addiction [10]. For example, animals with cocaine experience, but not after experience with food reinforcement, self-administer σ1 agonists (e.g., PRE-084 and (+)-Pentazocine) [76] at doses that do not induce DA release in the NAcSh [77] (reviewed in [10]).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this role, σ1 regulates both DA receptors signaling (DARs) via protein-protein interactions [7,8] and DA release in the striatum [9]. In contrast, there is evidence that cocaine and other stimulants may also engage σ1 independent of DA signaling and contribute to cocaine addiction [10], suggesting that redundant or complementary mechanisms exist to shape addiction-related phenotypes. However, no cellular mechanism has been identified so far.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been suggested that compounds with sigma receptor (sR) antagonist effects along with their affinity for the DAT will exhibit atypical DAT inhibitory effects similar to BZT . A number of previous studies indicated that sR antagonists can block several effects of cocaine, including locomotor stimulation, sensitization, and place conditioning (see review by Katz et al, 2011), and it is noteworthy that BZT analogs also have affinity for sRs Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The present study exploited a recent finding that subjects with cocaine self administration experience will also self administer the sR ligands (1)-pentazocine, PRE-084, and DTG (Katz et al, 2016) to examine in vivo potential antagonist effects and selectivity of several novel ligands (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Rats trained to self administer cocaine under fixed-ratio (FR) schedules continued to respond unabated when either (1)-pentazocine, PRE-084, or DTG was substituted for cocaine, although responding decreased with vehicle substitution. Further, pretreatment with several known nonselective sR antagonists blocked sR ligand self administration (Katz et al, 2016). This study used radioligand binding to assess subtype selectivity, and self administration in an attempt to distinguish subtype-selective agonist or antagonist effects of the novel sR ligands.…”
Section: Introductionmentioning
confidence: 99%